Employees’ Perception towards Online Training Program: A Case from A Hotel - Ni Komang Niko Pandeani; I Gusti Ngurah Agung Suprastayasa; Luh Putu Kartini (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2022)
Training has become a fundamental aspect in maintaining and even developing human resources in an organization. Training is a serious program that cost a lot, therefore the training program provided should be formulated based on the employee’s needs. Online training is one of the methods that is expected to give more flexibility and efficiency to the employees and the employers. As a luxury resort, Hotel X conducts online training and sets minimum hours to be achieved by the employees. However, based on the data obtained, most of employees do not achieve the minimum hours. Therefore, this research aims to analyse the online training program conducted at Hotel X in Bali. This research employed quantitative and qualitative methods to obtain the employees’ perceptions regarding the training course, content, instructor, and its relevance to their job. The quantitative data were obtained through a set of questionnaires administered to 180 samples and qualitative data were obtained by conducting interview with some employees and some managerial and senior staff. The result showed that, the training course and the training content provided are very good, the training instructor is qualified and very good, and the online training materials are relevant to the respondent’s job.